Large piece of terracotta foreign body embedded in the submandibular region for two years (Bangladesh Journal of Otorhinolaryngology, 2012)
An unusual case of a large piece of terracotta accidentally lodged in the neck and subsequently removed by operation 2 years later is reported. The novelty of this case lies in the facts that 1) a large terracotta foreign body lodged in the neck almost unnoticed for more than 2 years 2) route of entry of the foreign body to neck tissues was not by the more common route of perforation of aero-digestive tract from inside but piercing the neck from outside 3) the 2.5 cm object migrated to another site from apparent site of entry and 4) it was asymptomatic for 2 years despite being close to vital structures other than an inconspicuous cosmetic deformity. DOI: http://dx.doi.org/10.3329/bjo.v18i2.12026 Bangladesh J Otorhinolaryngol 2012; 18(2): 219-221